2022
DOI: 10.3390/su14148726
|View full text |Cite
|
Sign up to set email alerts
|

Key Initiatives for Digital Transformation, Green New Deal and Recovery after COVID-19 within the Construction Industry in Korea

Abstract: The low productivity of the construction industry has been identified as a chronic problem, and this has been exacerbated by recent environmental factors, including COVID-19 and climate change. As a response to these environmental changes, policies related to recovery after COVID-19, digital transformation, and the Green New Deal have been established worldwide, and related projects have been launched. These three issues may seem to have different goals but they are interrelated, and guidelines for the directi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Leadership backing It was found that top-down endorsement of digital change was crucial (Laukka et al, 2020). Leaders' prioritization and support of digital transformation projects increases the likelihood that those initiatives will receive funding, manpower, and other support from across the organization (Kim et al, 2022). Straightforward plan and direction Success in implementing digital transformation was found to depend on having a well-defined vision and plan (Kantabutra, 2020).…”
Section: Culture Within An Organizationmentioning
confidence: 99%
“…Leadership backing It was found that top-down endorsement of digital change was crucial (Laukka et al, 2020). Leaders' prioritization and support of digital transformation projects increases the likelihood that those initiatives will receive funding, manpower, and other support from across the organization (Kim et al, 2022). Straightforward plan and direction Success in implementing digital transformation was found to depend on having a well-defined vision and plan (Kantabutra, 2020).…”
Section: Culture Within An Organizationmentioning
confidence: 99%
“…In the post-pandemic period, governments around the world have established a series of policies and projects to promote digital transformation to solve the problems caused by COVID-19 and promote recovery. Countries, such as the United States, China, Germany, Japan, and the United Kingdom, have established digital industrial transformation policies to transform economic structures, create jobs, and enhance industrial competitiveness, and the construction industry has been particularly targeted to benefit from Artificial Intelligence (AI) and digital transformation policies [13]. These policies are in line with the Sustainable Development Goal (SDG) 8, which is to achieve sustainable economic growth and decent work and employment security, as well as Goal 9, which is to build infrastructure and promote sustainable industrialization, and these are in line with the measures proposed to complement the problems identified in this study [70].…”
Section: Practical Analysismentioning
confidence: 99%
“…During the COVID-19 pandemic, some major countries implemented measures related to construction costs and schedules to minimize losses [13]. For example, the United States halted work at all construction sites early in the outbreak and provided low-interest loans to small businesses and nonprofit organizations [14], while the United Kingdom delayed Value Added Tax (VAT) payments by about three months for all businesses, including construction firms, and published a public procurement policy that included information on prompt payment, contract advances, and contract changes to minimize losses due to COVID-19 [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shortage of skilled workers will be the biggest risk of construction supply falling short of demand according to urban sprawl [1], and challenges for site management, strengthened safety and healthrelated regulations, and rising construction costs due to supply chain disruption will result in major changes in the construction industry [2]. Furthermore, countries must reduce carbon dioxide emissions through energy saving, high-efficiency facilities, resource recycling, and reduction of environmental pollution to achieve the carbon neutrality according to the Paris Agreement, which took effect in 2016 [3]. There have been efforts to enhance the stagnant labor productivity, as an ongoing issue in the construction industry [4], by actively introducing information and communication technologies (ICTs), including technology related to the rapidly developing Fourth Industrial Revolution over recent years.…”
Section: Introduction 1background and Objectives Of Researchmentioning
confidence: 99%